Clathrochelate iron(II) tris-nioximates with non-equivalent capping groups and their precursors: synthetic strategies, X-ray structure, and reactivity. Issue 13 (3rd July 2017) - Zelinskii, Genrikh E.; Belov, Alexander S.; Chuprin, Alexander S.; Pavlov, Alexander A.; Vologzhanina, Anna V.; Lebed, Ekaterina G.; Bugaenko, Margarita G.; Voloshin, Yan Z.
Abstract: Template cross-linking of nioxime using equimolar amounts of boric and 4-vinylphenylboronic acids on an iron(II) ion as a matrix gave a mixture of mono- and divinyl-terminated clathrochelate products, which were chromatographically isolated in moderate yields and characterized by X-ray diffraction. The target complex FeNx3 (BOCH3 )(4-BC6 H4 CH=CH2 ) with non-equivalent capping groups was also obtained in a low yield using a transmetallation (re-boronation) of its dimethoxyboron-capped clathrochelate precursor. Re-boronation of the monomethoxyboron-capped cage complex with benzene-1, 4-diboronic acid as a bifunctional Lewis-acidic agent afforded mainly the clathrochelate product of its 1:1 re-boronation having a terminal B(OH)2 group. The iron(II) clathrochelate with labile triethylantimony capping groups underwent a transmetallation on the surface of silica gel giving an immobilized Sb, Si-capped macrobicyclic intermediate. Its desorption with 4-vinylphenylboronic acid unexpectedly gave the monovinyl-terminated iron(II) semiclathrochelate as the major product, isolated in a high yield; it was X-ray structurally characterized. The geometry of FeN 6 -coordination polyhedra of the above semi- and clathrochelates is intermediate between a trigonal prism and a trigonal antiprism; that of the monocapped iron(II) semiclathrochelate is more TAP-distorted and its pseudoencapsulated iron(II) ion is shifted from the center of this polyhedron by 0.02 Å in the direction of the capping boron atom. Abstract :